A fight for legitimacy: reflections on child protection reform, the reduction of baby removals, and child protection decision-making in Aotearoa New Zealand. (3rd July 2022) - Keddell, Emily; Fitzmaurice, Luke; Cleaver, Kerri; Exeter, Daniel
ABSTRACT: The rate of orders used to remove babies into the care of Oranga Tamariki reduced by more than half in Aotearoa New Zealand in 2019–2020 as a result of rapid reform, prompted by a high profile media case known as the 'Hawkes Bay case'. This case provoked social outrage, leading to media and public approbation, inquiries by state and Māori bodies, and advocacy from multiple organisations. Combined, these challenged the legitimacy of the child protection system and led to 'legitimacy work', that is, attempts by Oranga Tamariki to regain legitimacy with multiple publics. Access to the legal orders used to remove babies was immediately constricted. A sharp decline in baby removals followed, both overall and the disparities between Māori and non-Māori. The focus on disparity indicators alone, skewed by a focus on public legitimacy, had several unintended consequences. These included a lag between the constrictions on orders and other reforms aimed at addressing the inequities causing disparities, the diminishment of social worker discretion, and limited attention to other forms of system accountability. In the absence of other outcome indicators, particularly those defined by Māori and system-involved families, it is difficult to draw conclusions regarding the efficacy of these changes.